The role of autophagy in the progression of HIV infected cardiomyopathy - Sun, Yuting; Xu, Mengmeng; Duan, Qinchun; Bryant, Joseph L.; Xu, Xuehong (Frontiers in Cell and Developmental Biology, 2024)
Although highly active antiretroviral therapy (HAART) has changed infection with human immunodeficiency virus (HIV) from a diagnosis with imminent mortality to a chronic illness, HIV positive patients who do not develop acquired immunodeficiency syndrome (AIDs) still suffer from a high rate of cardiac dysfunction and fibrosis. Regardless of viral load and CD count, HIV-associated cardiomyopathy (HIVAC) still causes a high rate of mortality and morbidity amongst HIV patients. While this is a well characterized clinical phenomena, the molecular mechanism of HIVAC is not well understood. In this review, we consolidate, analyze, and discuss current research on the intersection between autophagy and HIVAC. Multiple studies have linked dysregulation in various regulators and functional components of autophagy to HIV infection regardless of mode of viral entry i.e. coronary, cardiac chamber, or pericardial space. HIV proteins, including negative regulatory factor (Nef), glycoprotein 120 (gp120), and transactivator (Tat), have been shown to interact with type II microtubule-associated protein-1 β light chain (LC3-II), Rubiquitin, SQSTM1/p62, Rab7, autophagy- specific gene 7 (ATG7), and lysosomal-associated membrane protein 1 (LAMP1), all molecules critical to normal autophagy. HIV infection can also induce dysregulation of mitochondrial bioenergetics by altering production and equilibrium of adenosine triphosphate (ATP), mitochondrial reactive oxygen species (ROS), and calcium. These changes alter mitochondrial mass and morphology, which normally trigger autophagy to clear away dysfunctional organelles. However, with HIV infection also triggering autophagy dysfunction, these abnormal mitochondria accumulate and contribute to myocardial dysfunction. Likewise, use of HAART, azidothymidine and Abacavir, have been shown to induce cardiac dysfunction and fibrosis by inducing abnormal autophagy during antiretroviral therapy. Conversely, studies have shown that increasing autophagy can reduce the accumulation of dysfunctional mitochondria and restore cardiomyocyte function. Interestingly, Rapamycin, a mammalian target of rapamycin (mTOR) inhibitor, has also been shown to reduce HIV-induced cytotoxicity by regulating autophagy-related proteins, making it a non-antiviral agent with the potential to treat HIVAC. In this review, we synthesize these findings to provide a better understanding of the role autophagy plays in HIVAC and discuss the potential pharmacologic targets unveiled by this research.